2021
DOI: 10.3389/fmed.2021.731102
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload in Patients With Heavily Transfused Sickle Cell Disease—Correlation of Serum Ferritin With Cardiac T2* MRI (CMRTools), Liver T2* MRI, and R2-MRI (Ferriscan®)

Abstract: The treatment of sickle cell disease (SCD) is mainly supportive, except for a minority, who receive bone marrow transplantation (BMT). Serum ferritin (SF) is routinely available but is notoriously unreliable as a tool for iron-overload assessment since it is an acute-phase reactant. Although blood transfusion is one of the most effective ways to deal with specific acute and chronic complications of SCD, this strategy is often associated with alloimmunization, iron overload, and hemolytic reactions. This study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…As a result, SCD patients may experience elevation of iron stores. In the present study, the majority of SCD children have ever been hemotransfused, which concur with the findings of several studies 24,25,43 Furthermore, we found that the increasing number of hemotransfusions significantly increased serum ferritin concentration. Specifically, it was demonstrated that SCD children who had received at least three hemotransfusions have higher median serum ferritin than those who received 1–2 and no hemotransfusions in that order, and the median difference was statistically significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, SCD patients may experience elevation of iron stores. In the present study, the majority of SCD children have ever been hemotransfused, which concur with the findings of several studies 24,25,43 Furthermore, we found that the increasing number of hemotransfusions significantly increased serum ferritin concentration. Specifically, it was demonstrated that SCD children who had received at least three hemotransfusions have higher median serum ferritin than those who received 1–2 and no hemotransfusions in that order, and the median difference was statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…However, the study has some limitations that can strengthen our findings when they are addressed in future studies. First, we did not perform liver biopsy or magnetic resonance interference which has been shown to provide an excellent assessment of elevated iron stores (iron overload) 43,45 to confirm our findings. Second, serum creatinine reactive protein levels were not measured to confirm the steady state of the study participants due to limited funds.…”
Section: Limitationsmentioning
confidence: 67%
“… 4 This may be because of the high erythropoietic drive causing severe hepcidin deficiency, which, in turn, leads to iron depletion of macrophages and lowering of the secretion of ferritin. 28 , 29 , 30 The incongruency between LIC and ferritin levels at baseline further highlights the high prevalence of iron overload even in patients who are not regularly transfused, and the importance of iron screening in all patients with PK deficiency. 4 …”
Section: Discussionmentioning
confidence: 99%
“…An average healthy person’s body has 4 g of iron, whereas people who receive multiple and frequent transfusions can accumulate 5 to 10 g annually. Long-term transfusion can lead to iron overload which may result in further complications including heart failure, growth retardation, endocrine problems and splenomegaly [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%